The Gibraltar’s problem evolution in the second half of XX - beginning XXI century - Natalia Lesiva (Cхід)
The given article is devoted to the complex analysis of Gibraltar's problem. The evolution of problem in context of relations between Great Britain and Spain are analyzed. The historical overview of Gibraltar's development is also researched. British and Spanish strategies in field of Gibraltar's problem are compared in the article. The public opinion in Gibraltar is also presented.